Effect of Service Quality on Consumer Satisfaction At PT. Pos Indonesia (Persero) Lubukpakam - Deni Pradana Syahputri (Institute of Computer Science (IOCS), 2019)
This study aims to determine whether the dimensions of service quality that is tangible, reliability, responsiveness, assurance, and concern affects customer satisfaction on PT POS Indonesia (Persero) Kontor POS Lubukpakam and analyze the most dominant factor in influencing customer satisfaction in PT POS Indonesia (Persero) Pos Kontor Lubukpakam. The population in this study are all consumers using PT POS Indonesia Lubukpakam. So based on calculations, the number of samples to be used in this study were 100 respondents. Based on the table it can be seen that most respondents were male as many as 63 people (63%), while the female respondents as many as 37 or (37%). To determine the sample size of the population can use formula variables. All the indicators used to measure the variables used in this study has the correlation value is greater than 0,197. From the results of this research indicate that all the indicators are valid. It can be shown from the many high satisfaction responses of respondents to the condition of each study variable. From these results further showed that the variable quality of service in the fifth dimension has a positive and significant impact on customer satisfaction. From the results of this research indicate that all the indicators are valid. It can be shown from the many high satisfaction responses of respondents to the condition of each study variable. From these results further showed that the variable quality of service in the fifth dimension has a positive and significant impact on customer satisfaction. From the results of this research indicate that all the indicators are valid. It can be shown from the many high satisfaction responses of respondents to the condition of each study variable. From these results further showed that the variable quality of service in the fifth dimension has a positive and significant impact on customer satisfaction.